العلاقات الأسرية كمتغير وسيط في العلاقة بين الذكاء الإيجابي والتطرف الفكري لدى عينة من طالبات جامعة الملك عبدالعزيز بجدة - سيف الدين، هدى برهان; خليفة، هدى بنت عاصم محمد (جامعة الملك عبدالعزيز, 2022)
الأهداف: هدفت الدراسة إلى التعرف على دور العلاقات الأسرية كمتغير وسيط في العلاقة بين الذكاء الإيجابي والتطرف الفكري لدى عينة من طالبات جامعة الملك عبد العزيز بمدينة جدة. المنهج: تم استخدام المنهج الوصفي الارتباطي وشملت عينة الدراسة على (239) طالبة من تخصصات علمية وأدبية، طبق عليهم كل من الأدوات التالية: مقياس العلاقات الأسرية من أعداد الباحثتين (2021)، ومقياس الذكاء الإيجابي، مقياس التطرف الفكري. النتائج: أسفرت الدراسة وجود علاقة ذات دلالة إحصائية بين العلاقات الأسرية وكل من الذكاء الإيجابي والتطرف الفكري لدى عينة الدراسة، وجود علاقة ذات دلالة إحصائية بين الذكاء الإيجابي والتطرف الفكري، كما انه من المتوقع أن يتغير حجم الارتباط لدى أفراد عينة الدراسة بين الذكاء الإيجابي والتطرف الفكري بعد العزل الإحصائي. الخاتمة: أوصت الدراسة بتفعيل دور الأسرة في توجيه الشباب ضد التطرف والإرهاب وأهمية إعداد الدورات التدريبية لتحسين مستوى مهارات الذكاء الإيجابي لدى طلاب الجامعة. Objectives: The study aimed to identify the role of family relationships as a mediating variable in the relationship between positive intelligence and intellectual extremism among a sample of female students at King Abdulaziz University in Jeddah. Method: The descriptive correlative approach was used, the sample consist of (239) female students from scientific and Arts colleges. Three measures were applied: Family relations index had been prepared by the two researchers, the Positive Intelligence test, and the intellectual extremism scale. Results: The overall results of the study revealed that: 1- there was a strong, positive correlation between family relationships and positive intelligence and negative correlation between family relationships and intellectual extremism, 2- There is a negative significant correlation between positive intelligence and intellectual extremism, 3- It is expected that the size of the correlation among the study sample members will change between positive intelligence and intellectual extremism after statistical isolation. Conclusion: The study concluded the importance of the family role which guide young people against extremism and terrorism, the importance of training courses to improve the level of positive intelligence skills among university students.
Keywords: طلبة الجامعة -- جامعة الملك عبدالعزيز -- الإرهاب الفكري -- المهارات الاجتماعية -- المناخ الأسري